Social Media Influencer: Clickbait Dalam Pusaran Etika Jurnalistik - Mochammad Sinung Restendy; Fahri Hilmi (Jurnal Komunika Islamika : Jurnal Ilmu Komunikasi dan Kajian Islam, 2021)
Information technology is increasingly developing. Internet networks provoke media convergence. Social media comes as a new mass media that is more interactive and more practical than the conventional one. Everyone can become a journalist in this era. The rapid progress of information technology not only brings efficiency in the process of reproduction of information, but also carries a variety of new risks. ‘Clickbait Journalism’ is one of many risks that is often done by influencers in the social media. How does Journalistic Law and Ethics study look at the phenomenon? Can influencers called as a journalist so they must obey the applicable ethics? Then, how does regulation respond to this phenomenon?